Modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane and preparation method thereof

The functionally modified concave and convex rod soil was prepared through one-step co-deposition reaction and the sulfonated polyether ether ketone was combined with high sulfonation degree, which solved the problems of high swelling rate and insufficient compatibility, and achieved high mechanical stability and proton conduction properties. Improvement.

CN119253002APending Publication Date: 2025-01-03HUBEI ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411301678.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the prior art, pure sulfonated polyether ether ketone has a high swelling rate under high temperature conditions, and the compatibility and conduction performance of the concave and convex rod soil and sulfonated polyether ether ketone are insufficiently improved when forming a proton exchange membrane.

Method used

Modified concave-convex soil functionalized by polydopamine and bissulfonate benzylamine was prepared by one-step co-deposition reaction, and combined with sulfonated polyether ether ketone with high sulfonation degree, to prepare modified concave-concave-concave-concave-concave-polyether ether ketone composite protons with sulfonated concave-concave-concave-polyether ether ketone sulfonated polyether ether ketone composite protons were prepared by a one-step co-deposition reaction. Exchange membrane to optimize the compatibility and conduction properties of modified concave and convex rod soil with sulfonated polyether ether ketone.

Benefits of technology

The low swelling rate and high proton conductivity under high temperature conditions are achieved, the mechanical stability and proton conductivity of the composite membrane are improved, and the problems of insufficient compatibility and conductivity are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane and a preparation method thereof, and the preparation method comprises the following steps: adding attapulgite into a buffer solution containing dopamine hydrochloride, then adding disulfonic acid benzidine, and carrying out a one-step co-deposition reaction to obtain polydopamine and disulfonic acid benzidine dual-functionalized modified attapulgite NH2 / SO3H (at) ATP; and mixing the modified attapulgite NH2 / SO3H (at) ATP, sulfonated polyetheretherketone and an organic solvent, uniformly dispersing to obtain a film-forming solution, and carrying out film casting to obtain the modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane. The modified attapulgite is prepared by a one-step co-deposition method, so that the compatibility between an inorganic attapulgite material and an organic polymer matrix is improved; and compounding the modified attapulgite with the sulfonated polyether ether ketone to effectively inhibit swelling of molecular chains of the sulfonated polyether ether ketone so as to prepare the composite proton exchange membrane with relatively high mechanical stability and high proton conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of proton exchange membranes, and in particular to a modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane and a preparation method thereof. Background Art

[0002] Fuel cells (FCs), as a new type of energy conversion device, have many advantages and are receiving increasing attention and research. According to the different types of fuel cell electrolytes, fuel cells can be divided into proton exchange membrane fuel cells (PEMFCs), alkaline fuel cells (AFCs), solid oxide fuel cells (SOFCs), phosphoric acid fuel cells (PAFCs), and molten carbonate fuel cells (MCFCs). Among them, proton exchange membrane fuel cells have the advantages of fast start-up speed, low operating temperature, high specific power and specific energy, and are the most promising fuel cells for commercialization. In the structure of proton exchange membrane fuel cells, proton exchange membranes (PEMs) are one of the core components, which mainly play an important role in conducting protons, blocking electrons, and separating the positive and negative poles. The performance of proton exchange membranes plays a decisive role in fuel cells. At present, many polyelectrolyte materials have been studied and applied as proton exchange membranes. Among them, sulfonated polyetheretherketone (SPEEK), as a fluorine-free organic polymer material, is an ideal choice to replace commercial perfluorosulfonic acid proton exchange membranes due to its excellent conductivity, simple preparation process and cheap source. As a non-fluorinated proton exchange membrane material, SPEEK has a certain rigidity due to the benzene ring structure in its structure. At the same time, the introduction of sulfonic acid groups helps to improve the conductivity. In general, in order to further improve the conductivity of SPEEK, increasing the degree of sulfonation is the most commonly used method, but too high a degree of sulfonation will also cause a high water absorption and swelling effect, which often leads to a high degree of swelling under relatively high temperature conditions (80°C) and cannot meet the use requirements. In order to take into account both structural stability and high conductivity, modifying SPEEK is a widely used strategy. At present, the main modification methods of SPEEK can be divided into three categories: inorganic modification, cross-linking modification and organic modification. Among them, the inorganic modification strategy has more advantages, and can accurately match the corresponding inorganic additives for modification according to the needs of specific performance enhancement. For example, by adding inorganic additives with strong water absorption, the water absorption rate of the composite membrane can be effectively enhanced, greatly improving its hydrophobicity. Alternatively, by introducing inorganic proton conductors, the proton transport performance of the composite membrane can be significantly improved. At the same time, the high stability and good dispersibility of inorganic additives can not only play the role of improving proton conductivity, but also play its role as a mechanical performance enhancer, and also help to greatly reduce the permeability of fuel. So far, metal oxides, carbon nanomaterials, inorganic proton conductors, natural clay materials, etc. have all been studied in the modification of proton exchange membranes.

[0003] As an excellent inorganic modified material, natural clay has the advantages of abundant sources, low price and stable structure. It has broad application prospects in the preparation of polymer / clay composite proton exchange membranes. As a natural clay material, attapulgite has a crystal structure between layered structure and chain structure. It is rich in magnesium, aluminum and silicate. The chemical formula is Mg5Si8O 20 (OH) 20 (OH2)4∙4H20, in which Mg(Al) is surrounded by two layers of oxygen-silicon to form an octahedral structure. It is precisely because of this structure of attapulgite that it has excellent mechanical properties. At the same time, attapulgite has the advantages of porous structure, large specific surface area, strong adsorption, and strong ion exchange performance, making it the only choice for reinforcing materials. However, as an inorganic material, attapulgite itself has poor compatibility with organic polymers, and the direct addition effect is not ideal. On the other hand, although the combination of attapulgite and polymer system can effectively improve its mechanical properties, attapulgite itself does not have the ability to improve proton transport performance. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, provide a modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane and a preparation method, and solve the technical problems in the prior art that the high-temperature swelling rate of pure sulfonated polyetheretherketone is high and the compatibility and conductivity performance are insufficiently improved when attapulgite is directly composited with sulfonated polyetheretherketone to form a proton exchange membrane.

[0005] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing a modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane, comprising the following steps: (1) adding attapulgite to a buffer solution containing dopamine hydrochloride, and then adding diphenylamine sulfonate to carry out a one-step co-precipitation reaction to obtain a modified attapulgite NH2 / SO3H@ATP dual-functionalized with polydopamine and diphenylamine sulfonate; (2) mixing the modified attapulgite NH2 / SO3H@ATP, sulfonated polyetheretherketone and an organic solvent, dispersing them evenly to obtain a membrane-forming liquid, and performing cast film formation to obtain a modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane.

[0006] In a second aspect, the present invention provides a modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane prepared by the above preparation method.

[0007] Compared with the prior art, the beneficial effects of the present invention include: The present invention uses polydopamine, diphenyl sulfonate and attapulgite as raw materials, and prepares modified attapulgite with dual functionalization of polydopamine and diphenyl sulfonate through a one-step co-precipitation modification strategy, thereby improving the compatibility between the inorganic attapulgite material and the organic polymer matrix; and then the modified attapulgite is composited with a sulfonated polyetheretherketone matrix to effectively inhibit the swelling of the sulfonated polyetheretherketone molecular chain, thereby preparing a composite proton exchange membrane with both high mechanical stability and high proton conductivity. DETAILED DESCRIPTION

[0008] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0009] Sulfonated polyetheretherketone (SPEEK) is a non-fluorinated proton exchange membrane material. Increasing its sulfonation degree is beneficial to improving conductivity, but too high a sulfonation degree will also cause a high water absorption and swelling effect, especially under high temperature conditions (80°C), and it will not be able to meet the use requirements due to high swelling. In order to take into account both structural stability and high conductivity, sulfonated polyetheretherketone (SPEEK) is usually modified. Among them, attapulgite, as a natural clay material, can theoretically be used as a reinforcing material, but attapulgite is an inorganic material, and its compatibility with organic polymers is poor, and attapulgite itself does not have the ability to improve proton transmission performance.

[0010] In view of the above problems, according to the structure and performance characteristics of attapulgite, the present invention adopts a simple modification strategy to prepare modified attapulgite (NH2 / SO3H@ATP) functionalized with polydopamine and bis(benzidine sulfonate) by a one-step co-precipitation reaction method of dopamine and bis(benzidine sulfonate) with attapulgite. Then (NH2 / SO3H@ATP) is compounded with SPEEK with a high degree of sulfonation to prepare a composite proton exchange membrane NH2 / SO3H@ATP / SPEEK. By optimizing the addition amount of NH2 / SO3H@ATP, a series of composite proton exchange membranes containing different mass fractions of NH2 / SO3H@ATP are prepared. While giving full play to the performance advantages of the attapulgite material itself, the problem of insufficient improvement in its compatibility with the organic polymer matrix and conductivity is solved.

[0011] In a first aspect, the present invention provides a method for preparing a modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane, comprising the following steps: (1) Adding attapulgite to a buffer solution containing dopamine hydrochloride, and then adding diphenylamine sulfonate, a one-step co-precipitation reaction is carried out to obtain modified attapulgite NH2 / SO3H@ATP functionalized with polydopamine and diphenylamine sulfonate; (2) The modified attapulgite NH2 / SO3H@ATP, sulfonated polyetheretherketone and an organic solvent are mixed and dispersed evenly to obtain a membrane-forming liquid, and a modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane is obtained by cast film formation.

[0012] Preferably, in step (1), the mass ratio of attapulgite, dopamine hydrochloride and diphenylamine sulfonate is (0.5-0.8): (0.5 g-1.0): (0.3-0.7).

[0013] Preferably, in step (1), the buffer solution containing dopamine hydrochloride is obtained by mixing dopamine hydrochloride, tris(hydroxymethyl)aminomethane, and water in a ratio of (0.5-0.8) g: (0.03-0.08) g: (100-150) mL. The specific mixing order can be selected according to the situation, for example, dopamine hydrochloride is dissolved in deionized water, and then tris(hydroxymethyl)aminomethane (tris) is added.

[0014] Preferably, in step (1), the one-step co-precipitation reaction is carried out under stirring at room temperature for 24 to 26 hours; After the one-step co-precipitation reaction, the modified attapulgite NH2 / SO3H@ATP was obtained by centrifugal separation, washing and drying.

[0015] Preferably, in step (2), the organic solvent comprises N,N-dimethylformamide (DMF); and the concentration of sulfonated polyetheretherketone in the membrane-forming solution is 0.02 to 0.04 g / mL.

[0016] Preferably, in step (2), the preparation step of sulfonated polyetheretherketone comprises: dissolving polyetheretherketone powder with concentrated sulfuric acid, stirring and reacting at 40-60°C for 4-6h, quenching with ice water after the reaction to obtain a white solid precipitate, washing and drying to obtain sulfonated polyetheretherketone; the ratio of polyetheretherketone powder to concentrated sulfuric acid is (8-12) g: 300 mL; and the mass fraction of concentrated sulfuric acid is 98%.

[0017] Preferably, in step (2), the mass ratio of modified attapulgite NH2 / SO3H@ATP to sulfonated polyetheretherketone is (8-80): (800-1000).

[0018] Further preferably, the added amount of modified attapulgite NH2 / SO3H@ATP is 1 to 5% of the mass of sulfonated polyetheretherketone.

[0019] Preferably, in step (2), the uniform dispersion is achieved by stirring at room temperature for 4 to 6 hours, and / or ultrasonic treatment for 30 to 40 minutes. The specific form of mixing the modified attapulgite NH2 / SO3H@ATP, sulfonated polyetheretherketone and organic solvent is not limited. The sulfonated polyetheretherketone and organic solvent may be first mixed to form a sulfonated polyetheretherketone solution, and the modified attapulgite NH2 / SO3H@ATP is added to the sulfonated polyetheretherketone solution; or the modified attapulgite NH2 / SO3H@ATP and sulfonated polyetheretherketone are each mixed with an organic solvent to form a solution / dispersion, and then the solution and the dispersion are mixed.

[0020] Preferably, in step (2), the film-casting process is to pour the film-forming liquid onto a clean glass plate and dry it at 60 to 80° C. for 24 to 36 hours.

[0021] In a second aspect, the present invention provides a modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane prepared by the above preparation method.

[0022] The main mechanism of action and advantages of the present invention: (1) In the preparation method of the present invention, polydopamine and diphenyl sulfonate and attapulgite are first used as raw materials, and a one-step co-precipitation modification strategy is used to prepare polydopamine and diphenyl sulfonate dual-functionalized modified attapulgite (NH2 / SO3H@ATP). Finally, the prepared NH2 / SO3H@ATP is added into a sulfonated polyetheretherketone (SPEEK) matrix with a high degree of sulfonation to prepare a composite proton exchange membrane with both high mechanical stability and high proton conductivity.

[0023] (2) On the one hand, dopamine hydrochloride plays a strong adhesion role to combine with attapulgite. At the same time, it introduces amino and sulfonic acid group structures through chemical reaction with diphenyl sulfonate, and then carries out organic functional coating modification on the attapulgite. The organic functional modification of the surface of attapulgite can not only solve the compatibility problem between attapulgite and SPEEK matrix, but also the introduced amino and sulfonic acid can form effective functional group interactions with the polymer matrix as active groups, such as acid-base interaction, which can effectively inhibit the swelling of SPEEK molecular chains with high sulfonation degree, and achieve the ideal synergistic effect system of attapulgite and SPEEK matrix, realize the role of attapulgite in enhancing mechanical properties, and the introduction of sulfonic acid group as conductive group can also help to further improve the conductive performance.

[0024] (3) The present invention prepares a series of composite proton exchange membranes containing different mass fractions of NH2 / SO3H@ATP by optimizing different NH2 / SO3H@ATP addition amounts.

[0025] The present invention is further described in detail below through specific examples and comparative examples; wherein the SPEEK used is prepared by the following method; 10g of polyetheretherketone (model: P201, purchased from Changchun Jida Special Plastic Engineering Research Co., Ltd.) powder was weighed and dissolved in 300mL concentrated H2SO4 (98wt%), and reacted at 50℃ with mechanical stirring for 5h. After the reaction, the obtained yellow-brown mixed solution was slowly poured into a large amount of ice water to quench, and a white powder solid precipitate was obtained. The taken out white solid was continuously rinsed with water until neutral, and then dried at 60℃ for 24h to obtain a yellow solid SPEEK. The nuclear magnetic hydrogen spectrum test showed that its sulfonation degree reached 80%.

[0026] Example 1 A method for preparing a modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane, comprising the following steps: (1) Take 0.5 g of dopamine hydrochloride and dissolve it in 100 mL of deionized water, weigh 0.05 g of tris(hydroxymethylaminomethane) buffer, then add 0.5 g of attapulgite powder and 0.5 g of diphenylamine sulfonate to obtain a mixed solution; use an air compressor to continuously introduce air into the mixed solution for stirring, react at room temperature for 24 h, then centrifuge the liquid after the reaction, wash the solid with deionized water, and dry the obtained solid in an oven at 60 °C to obtain modified attapulgite NH2 / SO3H@ATP.

[0027] (2) Dissolve 0.8g SPEEK in 20mL N,N-dimethylformamide to obtain SPEEK solution; in another beaker, disperse 8mg NH2 / SO3H@ATP evenly with 10mL DMF to obtain NH2 / SO3H@ATP dispersion. Add the NH2 / SO3H@ATP dispersion to the SPEEK solution and stir at room temperature for 5h to obtain a uniform film-forming solution. Pour the film-forming solution onto a clean glass plate and dry at 70℃ for 24h to form a film to obtain NH2 / SO3H@ATP-SPEEK-1%.

[0028] Example 2 Compared with Example 1, the only difference is that the amount of NH2 / SO3H@ATP added in step (2) is adjusted to 24 mg, and the other steps and conditions are the same as those in Example 1 to obtain NH2 / SO3H@ATP-SPEEK-3%.

[0029] Example 3 Compared with Example 1, the only difference is that the amount of NH2 / SO3H@ATP added in step (2) is adjusted to 40 mg, and the other steps and conditions are the same as those in Example 1 to obtain NH2 / SO3H@ATP-SPEEK-5%.

[0030] Example 4 Compared with Example 1, the only difference is that the amount of NH2 / SO3H@ATP added in step (2) is adjusted to 80 mg, and the other steps and conditions are the same as those in Example 1 to obtain NH2 / SO3H@ATP-SPEEK-10%.

[0031] Comparative Example 1 (Pure SPEEK membrane) A method for preparing a proton exchange membrane, comprising the following steps: Accurately weigh 0.8 g of SPEEK and dissolve it in 20 mL of N,N-dimethylformamide. Stir at room temperature for 5 h to form a uniformly dispersed film-forming solution. Pour the film-forming solution onto a clean glass plate and dry it at 70°C for 24 h to form a pure SPEEK film.

[0032] Comparative Example 2 (attapulgite-doped SPEEK membrane) A method for preparing a proton exchange membrane, comprising the following steps: Accurately weigh 0.8g of SPEEK and dissolve it in 20mL of N,N-dimethylformamide to obtain a SPEEK solution; in another beaker, use 10mL of DMF to evenly disperse 40mg of attapulgite to obtain an attapulgite dispersion. Add the attapulgite dispersion to the SPEEK solution, stir at room temperature for 5h to form a uniform film-forming solution, pour the film-forming solution onto a clean glass plate, dry at 70℃ for 24h to form a film, and obtain an attapulgite-doped SPEEK film.

[0033] Performance Testing The test conditions are described as follows: (1) Tensile strength and elongation at break: The membrane was cut into rectangular strips with a length × width = 40 mm × 20 mm and tested at room temperature. The tensile speed during the test was 20 mm / min.

[0034] (2) Swelling rate: The prepared composite film was cut into 10 mm × 20 mm pieces and placed in an electric constant temperature air drying oven at 80 °C for 12 h. The surface area A was measured and calculated. dry, Then immerse the weighed membrane in distilled water at room temperature for 24 hours, take it out and quickly wipe the surface moisture with filter paper, and measure and calculate its surface area A. wet The swelling ratio was calculated by the following formula:

[0035] (3) Proton conductivity: The resistance of the membrane was tested using the AC impedance method on a frequency response analyzer with a frequency scanning range of 1-10 7 Hz, the AC signal amplitude is 100mV. The cut membrane (1.5cm×2.5cm) was tested by two-electrode AC impedance method. Before the test, the membrane sample was placed in deionized water at room temperature to reach saturation. The proton conductivity σ (S / cm) of the membrane was calculated by the following formula:

[0036] Wherein, L and A are the distance between the two electrodes and the effective cross-sectional area of ​​the membrane to be tested between the two electrodes, respectively, and R is the resistance of the membrane, which is calculated from the data obtained from the AC impedance test.

[0037] The above test conditions were used to perform performance tests on the films obtained in various embodiments and comparative examples. The results are shown in Table 1 below.

[0038] Table 1 Performance test results of various embodiments and comparative examples

[0039] From Table 1, we can see that: (1) The swelling rate test shows that the swelling rates in Examples 1-4 are lower than those in Comparative Examples 1 and 2, indicating that NH2 / SO3H@ATP can effectively inhibit swelling, mainly because the acid-base interaction between NH2 / SO3H in the NH2 / SO3H@ATP structure and the sulfonic acid group in the SPEEK structure can effectively inhibit the swelling of the molecular chain. In Comparative Example 2, pure attapulgite was added, but due to the weak interface interaction with SPEEK, the swelling inhibition effect was not as good as that in Examples 1-4.

[0040] (2) The tensile strength test shows that Example 3 shows the highest tensile strength value of 45.6 MPa, which is significantly higher than that of Comparative Examples 1 and 2. This is mainly due to the strong interaction between NH2 / SO3H@ATP and SPEEK. The evenly dispersed NH2 / SO3H@ATP forms extensive physical cross-linking points in the polymer matrix, which effectively inhibits the movement of SPEEK molecular chains and improves the tensile strength.

[0041] (3) The conduction test shows that the high-temperature proton conductivity of Example 3 reaches 104.3 mS / cm, which is significantly higher than that of Comparative Examples 1 and 2. This is mainly because NH2 / SO3H@ATP introduces more proton action sites, interacts with the SPEEK matrix through acid-base interactions, and builds more proton transmission channels, thereby improving the conduction performance. Comparative Example 2 does not introduce groups with proton conduction properties, so the conductivity is not improved.

[0042] In summary, the present invention uses polydopamine and disulfonic acid benzidine and attapulgite through a one-step co-deposition coating strategy to prepare an amino / sulfonic acid dual-functionalized modified attapulgite material NH2 / SO3H@ATP, solves the compatibility problem between attapulgite and an organic polymer matrix, and at the same time imparts certain proton transport properties. Adding it to a SPEEK matrix with a high degree of sulfonation solves the problem of high swelling of SPEEK with a high degree of sulfonation leading to reduced structure and performance. Therefore, the present invention prepares a composite proton exchange membrane with excellent mechanical properties and high proton conductivity by compounding dual-functionalized modified attapulgite with sulfonated polyetheretherketone. The tensile strength of the composite proton exchange membrane obtained by the present invention is 35.2-45.6MPa, the swelling rate is 14-29%, and the proton conductivity at 80°C is 62.6-104.3 mS / cm.

[0043] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane, characterized in that: The following steps are involved: (1) Adding attapulgite to a buffer solution containing dopamine hydrochloride, and then adding diphenylamine sulfonate, a one-step co-precipitation reaction is carried out to obtain modified attapulgite NH2 / SO3H@ATP with dual functionalization of polydopamine and diphenylamine sulfonate; (2) The modified attapulgite NH2 / SO3H@ATP, sulfonated polyetheretherketone and an organic solvent are mixed and dispersed evenly to obtain a membrane-forming liquid, and a modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane is obtained by cast film formation.

2. The method for preparing the modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane according to claim 1, characterized in that: In step (1), the mass ratio of the attapulgite, the dopamine hydrochloride and the diphenyl sulfonate is (0.5-0.8): (0.5 g-1.0): (0.3-0.7).

3. The method for preparing the modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane according to claim 1, characterized in that: In step (1), the buffer solution containing dopamine hydrochloride is obtained by mixing dopamine hydrochloride, trishydroxymethylaminomethane and water in a ratio of (0.5-0.8) g: (0.03-0.08) g: (100-150) mL.

4. The method for preparing the modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane according to claim 1, characterized in that: In step (1), the one-step co-precipitation reaction is carried out under stirring at room temperature for 24 to 26 hours; After the one-step co-precipitation reaction, the modified attapulgite NH2 / SO3H@ATP was obtained by centrifugal separation, washing and drying.

5. The method for preparing the modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane according to claim 1, characterized in that: In step (2), the organic solvent includes N,N-dimethylformamide; and the concentration of sulfonated polyetheretherketone in the membrane-forming solution is 0.02 to 0.04 g / mL.

6. The method for preparing the modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane according to claim 1, characterized in that: In step (2), the preparation step of the sulfonated polyetheretherketone comprises: dissolving polyetheretherketone powder with concentrated sulfuric acid, stirring and reacting at 40-60°C for 4-6 hours, quenching with ice water after the reaction is completed to obtain a white solid precipitate, and washing and drying to obtain the sulfonated polyetheretherketone; the ratio of polyetheretherketone powder to concentrated sulfuric acid is (8-12) g: 300 mL; and the mass fraction of concentrated sulfuric acid is 98%.

7. The method for preparing the modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane according to claim 1, characterized in that: In step (2), the mass ratio of the modified attapulgite NH2 / SO3H@ATP to sulfonated polyetheretherketone is (8-80): (800-1000).

8. The method for preparing the modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane according to claim 7, characterized in that: The added amount of the modified attapulgite NH2 / SO3H@ATP is 1-5% of the mass of the sulfonated polyetheretherketone.

9. The method for preparing the modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane according to claim 1, characterized in that: In step (2), the uniform dispersion is achieved by stirring at room temperature for 4 to 6 hours, and / or ultrasonic treatment for 30 to 40 minutes; The film-casting process is to pour the film-forming liquid onto a clean glass plate and dry it at 60 to 80° C. for 24 to 36 hours.

10. The modified attapulgite sulfonated polyetheretherketone composite proton exchange membrane obtained by the preparation method according to any one of claims 1 to 9.